WEDDING IMAGERY IN THE TALOS EPISODE: APOLLONIUS RHODIUS, ARGONAVTICA 4.1653–88. (12th February 2019) - Cassidy, Sarah
Abstract : At Argon. 4.1653–88, Medea steps forward among the Argonauts and asserts that their harbourage on Crete will not be blocked by the bronze giant Talos, who stands menacingly throwing rocks at their ship. She claims that she alone can subdue him, and then steps forward and proceeds to do so. Using a sequence of 'magical' ritualistic acts, she causes Talos to scrape his vulnerable heel on a rock and fall down dead, as the ichor pours from his wound. This scene is the last in which Medea appears in the epic, and accordingly it forms the final opportunity to bridge the gap between the Medea of the Argonautica and the future Medea, one whose actions are already well known from such works as Pindar's fourth Pythian Ode and Euripides' Medea . The importance for Apollonius to create a plausible transition between the Medea of earlier myth and the Argonautic Medea is evident. A clear-cut break from tradition would allow Medea to become an alternative Medea, perhaps akin to the alternative portrayal of Helen by Euripides; a continuation would allow corroboration with earlier sources, which would lend authority and validation to Apollonius' version. It is now the common consensus that Apollonius tried, however successfully, to bridge the gap between a young and an adult Medea and between tradition and innovation in her character.